2015
DOI: 10.3986/ac.v44i1.1739
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Relationships Between Karst Terrains and Social Features by the Example of Gömör-Torna Karst (Hungary-Slovakia)

Abstract: IzvlečekUDK 911.5:551.435.8(439+437.6) Tamás Telbisz, Zsolt Bottlik, László Mari & Alena Petrvalská: Raziskovanje odnosov med kraško pokrajino in socialnimi funkcijami: Primer kraškega območja Gömör-Torna (Madžarska-Slovaška) Odnosi med človekom in okoljem imajo v primeru kraških okolij nekatere posebne značilnosti. Ta so običajno manj gosto naseljena predvsem zaradi hidroloških, topografskih in pedoloških posebnosti. Vendar pa je vpliv naravnih dejavnikov kraških pokrajin na družbeno-gospodarski razvoj redko … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…The next decade was also characterized by a significant decrease (2435 people), but the rate of decrease was smaller (27%). Since that time, there is an even smaller rate but permanent decrease that led to the present situation of 3.6 p/km 2 population density, which is very low, similarly to other karst terrains (Telbisz et al 2015). The dramatic depopulation can be also characterized by the fact that while in 1928 there were only 3 settlements with less than 100 inhabitants (out of 45), there are now (in 2011) 32.…”
Section: Rural Depopulation Trendsmentioning
confidence: 84%
See 1 more Smart Citation
“…The next decade was also characterized by a significant decrease (2435 people), but the rate of decrease was smaller (27%). Since that time, there is an even smaller rate but permanent decrease that led to the present situation of 3.6 p/km 2 population density, which is very low, similarly to other karst terrains (Telbisz et al 2015). The dramatic depopulation can be also characterized by the fact that while in 1928 there were only 3 settlements with less than 100 inhabitants (out of 45), there are now (in 2011) 32.…”
Section: Rural Depopulation Trendsmentioning
confidence: 84%
“…The present study, in turn, examines the effect of karst on social processes, based on the following thesis: due to the unfavourable natural conditions (poor soils, lack of water, special relief conditions), karst terrains have always been relatively sparsely populated, and they have been severely affected by recent depopulation processes. Naturally, there are exceptions, but the validity of the above statement has been demonstrated for several karst areas in the Carpathian Basin (Telbisz et al 2015(Telbisz et al , 2016, or in the Balkan (Pejnović & Husanović-Pejnović 2008;Milošević et al 2010;Telbisz et al 2014), and this trend is generally valid for a large part of the Mediterranean region (McNeill 1992;Vogiatzakis 2012). It is noted that the effects of karst and of the mountainous environment are often intermingled and in most cases it is not possible to discriminate them.…”
Section: Introductionmentioning
confidence: 90%
“…As for the microregion, the Aggtelek Karst has always been a sparsely inhabited area due to the relatively harsh natural settings of the karst terrain, and its population stagnated or even slightly decreased during the nineteenth century. In the twentieth century, one can observe a moderate increase until 1970, but since that time there has been a strong downward trend (Telbisz et al 2015;Fig. 5).…”
Section: Social Situation Of the Aggtelek Karst Microregion Settlementsmentioning
confidence: 99%
“…Recently, geoparks have become the flagships of geoconservation, and sustainable development is one of the main aims of geoparks (Zouros and McKeever 2004;McKeever and Zouros 2005;Farsani et al 2011;Lazzari and Aloia 2014;Han et al 2018). In many cases, karst terrains are economically underdeveloped areas (Telbisz et al 2014(Telbisz et al , 2015(Telbisz et al , 2016a(Telbisz et al , 2019, but they have varied attractions from the perspective of geotourism (Dowling and Newsome 2006). As Cigna and Forti (2013) stated, caves are the most important geotouristic features in the world.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of possibilism states that the environment sets certain constraints or limitations, but culture is otherwise determined by social conditions. The study of statistical relationships between topographic factors and the spatial distribution of population is called "hypsographic demography" by some authors (Small and Cohen 2004;Patterson and Doyle 2011), and we also applied this approach in our previous studies (Telbisz et al 2014(Telbisz et al , 2015(Telbisz et al , 2016(Telbisz et al , 2019. Several researchers demonstrated that in many cases, there exist statistically significant correlations between depopulation and topographic factors like elevation or slope (Kohler et al 2017;Latocha et al 2018).…”
Section: Introductionmentioning
confidence: 96%